Dielectric spectroscopy analysis of molecular reorientation in dye doped nematic liquid crystals having different preliminary orientation - Okutan, M; San, SE; Köysal, O (Elsevier Sci Ltd, 2005)
Reorientation tendencies of liquid crystal (LC) molecules are investigated for two different fundamental orientation configurations that are known as homogenous (HG) and homeotropic (HT). A hybrid LC content, including red and blue dyes together, is employed in these two cells enabling measurements in different spectral regions by two different lasers. Influence of preliminary orientation on the behaviors of molecules under dark and illuminated circumstances is extracted from the performed measurements. Dielectric anisotropy is also studied for the mentioned conditions and its dependency is quantitatively estimated by capacitive measurements. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: liquid crystals; dye doped; dielectric anisotropy